Computer Network Design and Applications for West Java Legislative Elections - Usman, Muhammad Lulu Latif; Supriyadi, Asep Adang; Wijaya, Satria Dhaniswara Rahsa; Herdianto, Bachtiar (Indonesian Journal of Information Systems, 2024)
Legislative elections or Pileg are an annual schedule that is routinely held in Indonesia for five years. The concept of technology 4.0 has a huge opportunity to be applied in the legislative election process in this modern era. Legislative elections that use digital devices connected in such a way have more advantages than legislative elections that use conventional methods. The application of technology 4.0 in legislative elections has advantages in terms of effectiveness, data processing speed, and costs. The design of the legislative election system is made using a network where each polling station will be provided with one server to accommodate votes at the polling station. Then the server synchronizes the data to a central server to calculate the final results obtained. The server is built using the text-based Ubuntu Linux operating system. The application used is web-based, with the programming languages used being HTML, PHP, CSS, and Javascript. The test data shows that the time required for the system to complete each stage of the legislative election process is relatively faster than conventional legislative elections. So it can be concluded that the design of the legislative election system has met the requirements to accelerate the legislative election process. This research uses an SDLC system with a prototype model. Tests are carried out using BlackBox testing to test the suitability of the application with application access.